RUANG KREATIF DIGITAL - Cindy Valenci; Tony Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Millennial are considered as a generation that could integrate with technology better than previous generation. The presence of technology is something that can’t be removed in this generation. They live a life which always have been connected with technology, and also entitled as net generation that has the ability to be connected with various worlds. With today’s advancement, presence of technology in millennial generation affect workshop machinery with digital technology. The formed program is expected to be able to answer the characteristics of the millennial generation in the digital technology sector by providing workshops with education and training space for start-ups. The designed space system consists of several programs combined based on analysis of Millennial generation needs and workspace typology analysis. The choice of location is chosen based on several criteria; based on the location of the city center, close to many presences of the millennial, and located in where public transportation is easily accessible. The design created will have the concept of a digitally made product, so that it attracts visitors. The rental system is applied in buildings based on the following spaces with supporting facilities. Placement and orientation will be adjusted according to the results of the site analysis, and to create an environmentally friendly building, the ground floor building will be half open and greenery concept around the site.       AbstrakGenerasi milenial termasuk generasi yang bisa berintegrasi dengan teknologi dari generasi sebelumnya. Hadirnya teknologi bagaikan sesuatu yang tidak dapat dipisahkan dengan generasi ini. Semasa hidup yang selalu terkoneksi dengan digital online maka generasi ini disebut juga net generation yang dapat terkoneksi dengan berbagai dunia. Secara perkembangan zaman, hadirnya teknologi dalam generasi milenial mempengaruhi mesin peralatan bengkel kerja dengan teknologi digital. Program yang terbentuk diharapkan dapat menjawab karakteristik generasi milenial dalam sektor teknologi digital dengan penyediaan bengkel kerja serta memberikan ruang edukasi dan pelatihan bagi start-up. Sistem ruang yang dirancang terdiri dari beberapa program yang digabungkan berdasarkan analisa kebutuhan generasi milenial serta berdasarkan analisa tipologi ruang kerja. Pemilihan lokasi dipilih berdasarkan beberapa kriteria; berdasarkan peletakannya di pusat kota, dekat dengan banyaknya keberadaan generasi milenial, serta peletakannya yang mudah dijangkau dengan kendaraan umum. Desain yang dibuat akan memiliki konsep suatu hasil produk dari digital, sehingga menarik pengunjung. Sistem sewa yang diberlakukan dalam bangunan berdasarkan ruang-ruang berikut dengan fasilitas penunjangnya. Penempatan dan orientasi akan disesuaikan oleh hasil analisa tapak dan untuk menciptakan bangunan yang ramah lingkungan, lantai dasar dibuat setengah terbuka dan adanya penghijauan disekitar tapak.